2001
DOI: 10.1021/bi0024456
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Flippase Activity of the Reconstituted P-Glycoprotein Multidrug Transporter

Abstract: The P-glycoprotein multidrug transporter acts as an ATP-powered efflux pump for a large variety of hydrophobic drugs, natural products, and peptides. The protein is proposed to interact with its substrates within the hydrophobic interior of the membrane. There is indirect evidence to suggest that P-glycoprotein can also transport, or "flip", short chain fluorescent lipids between leaflets of the membrane. In this study, we use a fluorescence quenching technique to directly show that P-glycoprotein reconstitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
151
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(164 citation statements)
references
References 64 publications
12
151
1
Order By: Relevance
“…This evidence is confirmed by reconstitution experiments, in which MsbA has been shown to translocate a wide variety of fluorescent-labeled phospholipids, albeit with low activity [72]. In the case of P-glycoprotein, studies in cell lines and reconstituted systems have suggested the involvement of this protein in transport of a variety of phospho-and glycolipids [65,70,[89][90][91]. However, this protein was first identified as the multidrug resistance transporter responsible for the inefficiency of long-term pharmacological treatments [92].…”
Section: Putative Catalytic Mechanism Of Abc Transporters Of the "Expmentioning
confidence: 80%
“…This evidence is confirmed by reconstitution experiments, in which MsbA has been shown to translocate a wide variety of fluorescent-labeled phospholipids, albeit with low activity [72]. In the case of P-glycoprotein, studies in cell lines and reconstituted systems have suggested the involvement of this protein in transport of a variety of phospho-and glycolipids [65,70,[89][90][91]. However, this protein was first identified as the multidrug resistance transporter responsible for the inefficiency of long-term pharmacological treatments [92].…”
Section: Putative Catalytic Mechanism Of Abc Transporters Of the "Expmentioning
confidence: 80%
“…The mechanism of fatty acid transport by these peroxisomal proteins has not been elucidated. Some evidence indicates that the human ABC protein P-glycoprotein acts as a flippase that transports phospholipids between leaflets of the plasma membrane (Romsicki and Sharom, 2001), although other mechanisms also have been suggested for protein P-glycoprotein and other ABC transporters (van Veen and Konings, 1997;van Veen, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In liposomes containing purified ABCB1 in an inverted orientation, an ATP-dependent transport activity was found when measuring the movement of fluorescent lipid analogues from outside to the inside of the liposomes. This lipid transport activity was inhibited by ABCB1 drug substrates; thus, drug and lipid transport activities are similar processes (Eckford & Sharom, 2005;Romsicki & Sharom, 2001). According to data in the literature, ABCB1 can also transport ceramides and sphingolipids (Clay & Sharom, 2013;Coleman et al, 2013;Radeva et al, 2005;Sharom, 2014), indicating a wide substrate specificity of ABCB1 also for lipid molecules.…”
Section: P0255mentioning
confidence: 91%